2020
DOI: 10.1002/ejoc.202000251
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid Promoted Thermal‐Ring‐Rearrangement of Fluorenopyrans to 2‐(1H‐Inden‐3‐yl)‐9H‐fluoren‐3‐ols Bearing Two All‐Carbon‐Quaternary Centres

Abstract: 4-Aryl-fluorenopyrans bearing quaternary centre at C2 and C6 positions underwent a thermal-ring-rearrangement with a catalytic amount of pTsOH to furnish 2-(1H-inden-3-yl)-9H-fluoren-3-ols with two all carbon-quaternary centres, in which one is retained and the other is created. Interestingly, these compounds exhibit atropisomerism, when they have at [a] Figure 2. Acidochrmoic nature of 1a. Results and DiscussionTo find out the suitable reaction conditions of the ring-rearrangement reaction, we have selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…We commenced our study by examining the intramolecular C­(sp 2 )–H oxacyclization of 1-(1,1-dimethyl-1 H -inden-3-yl)­naphthalen-2-ol ( 1a ) (which was prepared using a reported method) to 8,8-dimethyl-8 H -indeno­[2,1- b ]­naphtho­[1,2- d ]­furan ( 2a ). A detailed study of reaction conditions indicated that heating 1a in 1:1 DMSO/AcOH at 140 °C with 10 mol% CuI in an open flask furnished the maximum yield of 2a , 92% (Table ).…”
Section: Resultssupporting
confidence: 75%
“…We commenced our study by examining the intramolecular C­(sp 2 )–H oxacyclization of 1-(1,1-dimethyl-1 H -inden-3-yl)­naphthalen-2-ol ( 1a ) (which was prepared using a reported method) to 8,8-dimethyl-8 H -indeno­[2,1- b ]­naphtho­[1,2- d ]­furan ( 2a ). A detailed study of reaction conditions indicated that heating 1a in 1:1 DMSO/AcOH at 140 °C with 10 mol% CuI in an open flask furnished the maximum yield of 2a , 92% (Table ).…”
Section: Resultssupporting
confidence: 75%